URINARY STONE RISK PROFILE IN STONE FORMER PATIENT - Prasetyo, Tommie; Birowo, Ponco; Rasyid, Nur (Indonesian Urological Association, 2015)
Objective: We were comparing the urinary stone risk profiles in stone former subjects group with normal population (non stone-former) group. Material & method: In this study, each group consist of 10 subjects. Urine samples used was a 24-hour-urine. All subjects in this study were previously informed and voluntarily participating. Inclusion criteria in this study were adult, stone free, residing in Jakarta. Measurement was performed in Department of Molecular Biology and Biochemistry Faculty of Medicine Indonesia University. Statistical analysis was performed using SPSS 20 (Chicago, USA) with Student’s t-test or Mann-Whitney (p < 0.05 was considered significant). Results: There was a significant difference in the mean age of two groups with no significant difference in weight and height. Significant difference (p < 0.05) in urinary profile was found in urea, uric acid, chloride, potassium, phosphate, and ammonia. Conversely, we found no significant differences (p > 0.05) in sodium, creatinine, calcium, magnesium, oxalate, and citrate levels. Conclusion: There were no significant differences in urinary stone promoting and inhibiting factors between two groups. Bigger number of sample size with better sampling method must be conducted for future studies.